(untitled) (Italiano LinguaDue, 2025)
Il contributo riflette sull’educazione linguistica nel primo ciclo di istruzione, partendo dai repertori linguistici degli allievi per sviluppare percorsi interdisciplinari con obiettivi comuni. Dall’anno scolastico 2018-2019, queste attività si svolgono in un istituto comprensivo della provincia di Bolzano in un contesto di plurilinguismo endogeno (insegnamento in italiano e tedesco) ed esogeno (lingue degli allievi). I materiali utilizzati mostrano un percorso di organizzazione delle conoscenze tramite riflessioni metalinguistiche spontanee in un contesto plurilingue. Dalla scuola dell’infanzia alla secondaria di primo grado, le attività integrate favoriscono la riflessione metalinguistica esplicita attraverso racconti in lingue “inventate”, riflessioni semantico-lessicali e morfologiche in italiano, matematica e scienze. Il contributo evidenzia lo sviluppo delle capacità di ragionare sulla lingua ed esplicitare le riflessioni metalinguistiche. Te To Tè? Constructing/building and sharing language experience The contribution gives insights on language education in primary and secondary school, starting from the learners’ linguistic repertoires to develop projects with common interdisciplinary objectives. The activities have been taking place from school year 2018-19 in a comprehensive school in South Tyrol, Italy, in a context of endogenous (subjects taught in Italian and German) and exogenous multilingualism (the students’ heritage languages). The materials show a path of knowledge organization through spontaneous metalinguistic reflections in a multilingual context. From kindergarten to lower secondary school, integrated activities promote explicit metalinguistic reflection through stories in “invented” languages, semantic-lexical and morphological reflections in Italian, mathematics, and science. The contribution highlights the development of learners’ ability to reason about language and articulate metalinguistic reflections.